5G leading digital technology enables the rapid development of agricultural Internet - Gang AN; Yunyong ZHANG; Jinshi WANG; Xuehong YANG (Dianxin kexue)
With the development of “new infrastructure”, digital village construction of China has ushered in a new climax, digital village of building is not only the strategic direction of rural revitalization, but also an important content of building a digital China.Agricultural Internet is a key link in the construction of digital village.As 5G and other digital technologies continue to penetrated into various fields of agricultural production, China’s agricultural Internet has entered a new stage of rapid development.Focusing on the new changes brought by 5G and other digital technologies to agricultural Internet, through 5G, satellite remote sensing, UAV, artificial intelligence and machine vision to promoted the digital transformation of agricultural production and operation, the future development status and trend of agricultural Internet in China were deeply discussed.